The Correlation Between Quality of Life and Acceptability of Disability in Patients With Facial Burn Scars - Zhang, Xiuni; Liu, Yuan; Deng, Xiaohong; Deng, Chengsong; Pan, Yunfeng; Hu, Ailing (Frontiers in Bioengineering and Biotechnology, 2019)
The purpose of our research is to understand the status of the quality of life and level of disability acceptance in patients with facial burn scars and to explore the correlation between quality of life and disability acceptance and how to improve nursing care for these patients. Patients with facial burn scars were investigated in an outpatient clinic of tertiary hospitals from September 2015 to February 2016. A cross-sectional survey was conducted. The questionnaires used included demographic data and investigations using the burn scars table, Burn-Specific Health Scale-Brief (BSHS-B), and acceptance disability scale (ADS). Differences between participants in terms of demographic characteristics, quality of life, and disability acceptance were assessed using two-tailed independent t-tests. The total score of quality of life and disability acceptance in facial burn scar patients was 137.06 ± 17.05 and 185.68 ± 23.74, respectively. The results of Spearman correlation analysis showed that the overall quality of life score of facial burn scar patients was positively correlated with disability acceptance (r = 0.245, p = 0.007). The quality of life of facial burn scar patients will improve with the improvement of disability acceptance level. Therefore, medical staff can improve the quality of life of patients by improving their disability acceptance level.